RETROGRADE JEJUNOGASTRIC INTUSSUSCEPSION – REPORTING A RARE CASE. - DR PRAN GOPAL SARKAR MS (International Journal of Pharma and Bio Sciences, 2013)
Retro grade jejunogastric intussusception is a rare condition, that follows after any sort of gastrojejunal anastomosis, where the loop of jejunum intussuscepts into the cavity of stomach through the anastomotic stoma. It is so rare that less than 200 cases have been reported till now in literature since it was first reported in 1914. A patient was referred to our endoscopy centre for Upper GI endoscopy on 2nd day of hospital admission with a H/O pain abdomen and haematamesis. diagonostic endoscopy spotted the condition rapidly. A non gangrenous but contused retrograde jejunogastric intussusception (RJGI) was possible to diagnose within a short time of hospital admission by UGI endoscopy. A delayed diagnosis always caries high mortality in these cases. Patients with H/O previous stomach operation presenting with upper abdominal pain and With or without haematamesis should rise the clinical suspicion of Retrograde jejunogastric intussception and diagnostic UGI endoscopy should be done as soon as possible .It is most rapid diagnostic method for RJGI and thus saving the patient from delayed intervention and high mortality.